2018
DOI: 10.1080/15476286.2018.1445404
|View full text |Cite
|
Sign up to set email alerts
|

A stable tRNA-like molecule is generated from the long noncoding RNA GUT15 in Arabidopsis

Abstract: The Arabidopsis GUT15 RNA belongs to a class of noncoding RNAs that are expressed from the intergenic regions of protein-coding genes. We show that the RNA polymerase II transcribed GUT15 transcript serves as a precursor for two stable RNA species, a tRNA-like molecule and GUT15-tRF-F5, which are both encoded by the final intron in the GUT15 gene. The GUT15-encoded tRNA-like molecule cannot be autonomously transcribed by RNA polymerase III. However, this molecule contains a CCA motif, suggesting that it may en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It was noteworthy that some targets of A. membranaceus MIR156 were homologues of Arabidopsis GUT15 ( AtGUT15 , AT2G18440), a long noncoding RNA [42].…”
Section: Resultsmentioning
confidence: 99%
“…It was noteworthy that some targets of A. membranaceus MIR156 were homologues of Arabidopsis GUT15 ( AtGUT15 , AT2G18440), a long noncoding RNA [42].…”
Section: Resultsmentioning
confidence: 99%
“…5B, Additional File 3). LncRNAs containing structural RNA sequences have been previously identified in other organisms including humans (sno-lncRNAs) and plants (lncRNA containing a tRNA-like molecule) [28][29][30]. We also identified examples where more than one structural RNA sequence was contained within a single lncRNA.…”
Section: Some Lncrnas Contain Structural Rna Sequencesmentioning
confidence: 90%
“…It was later found that the stability of the transcript is more tissue specific [94]. The primitive arabidopsis GUT15 transcript serves as a precursor for two stable RNAs, one of which is a TLS [92]. This TLS is CCA modified and has an inhibitory effect on the slicing of its host intron [92].…”
Section: Tlss In Noncoding Rnasmentioning
confidence: 99%
“…The primitive arabidopsis GUT15 transcript serves as a precursor for two stable RNAs, one of which is a TLS [92]. This TLS is CCA modified and has an inhibitory effect on the slicing of its host intron [92]. Canonical tRNAs that are encoded within introns, however, have no similar effect [92], suggesting that this may be a function independent of tRNA similarity.…”
Section: Tlss In Noncoding Rnasmentioning
confidence: 99%